Marketing strategy of Skyeng - Sidorov, Grigory; Halík, Jaroslav, 1961-; Šípková, Martina; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2023)
My thesis is about the business named Skyeng, its marketing strategy and position in the market. There are 3 chapters in the paper. In the first chapter there will be theoretical knowledge about concepts of marketing, types of marketing strategies and the methodology of choosing the one. The second chapter will be dedicated to the Skyeng, its characteristics and the vision of the company, as well as their target group. The final chapter will consist of some recommendations for Skyeng’s current strategy and some development ideas. The main questions of my thesis are: What is the marketing strategy of Skyeng? What is their position in the market? How their marketing strategy can be improved? According to all the research made, the Skyeng uses a mix of content, mail and communication strategies in order to keep their brand awareness on a high level. For the past couple of years Skyeng is an absolute leader in the market and their main goal is to keep the leadership and stay far from competitors. However, the company can improve its performance even more by adjusting their services towards changing target group and by using modern technologies (such as AI bots) in their communication with students.
Vedoucí práce: Jaroslav Halík
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses